PENGARUH KUALITAS PRODUK DAN BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KARET BAN MERK MBS PADA PT. GEMAR SUKAWATI INDAH MEDAN - Hernawaty (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2017)
The quality of the product and marketing mix are the things that can affect the purchasing decisions made by the buyer. This happened at the PT. Gemar Sukawati Indah Medan, a company engaged in the sale of rubber tires having a problem with the quality of products and the promotion mix. The theories used in this research are theories of Marketing Management, related to the theory about the quality of the product, the theory of the promotional mix, and the theory of purchasing decisions. This research method is quantitative approach and type of research is descriptive quantitative. Data collection was performed by interviews, questionnaires and documentation. Method of data analysis used is multiple linear regression analysis. The population data are all customers of PT. Gemar Sukawati Indah Medan consisting of 92 respondents, of which 30 respondents were used to test the validity and the remaining 62 respondents were used for the study samples. The quality of products and the promotion mix function as independent variables and then the purchase decision as the dependent variable. The result of study on the hyptohesis stated that the quality of products and the promotion mix simultaneously have a significant effect of purchasing decisions in which F-observed 35.018 larger than F table (3.15). Partially, product quality has a significant effect on purchasing decisions in which results T-observed 2,509 higher than T table (2,001) and the promotion mix partially also has a significant effect on purchasing decisions because T-observed of 4,313 is higher than the value of T- table (2.001) , This shows that the promotional mix is ​​a more dominant factor affecting purchasing decisions.